The Celsa Case - A Take-Over Lender-Led Non-Consensual Restructuring Plan - Thery, Adrian; Lama, Carlos (European Insolvency and Restructuring Journal, 2024)
Court approval of a lender-led non-consensual restructuring plan filed by financial creditors without the debtor’ support and challenged by all the shareholders. The plan allows creditors to take control of the equity post-restructuring and to wipe-out pre-existing shareholders. The Court found that the necessary requirements were met due to the existence of imminent insolvency and the shareholders being "out of the money." This is a landmark case in Spain regarding the new fairness test, based on an agreement between the affected classes or, in its absence, on the enterprise value and its distribution amongst the insolvency ranks following the absolute priority rule.